Kinetic Modeling of the Genetic Information Processes in a Minimal Cell - Thornburg, Zane R.; Melo, Marcelo C. R.; Bianchi, David; Brier, Troy A.; Crotty, Cole; Breuer, Marian; Smith, Hamilton O.; Hutchison, Clyde A.; Glass, John I.; Luthey-Schulten, Zaida (Frontiers in Molecular Biosciences, 2019)
JCVI-syn3A is a minimal bacterial cell with a 543 kbp genome consisting of 493 genes. For this slow growing minimal cell with a 105 min doubling time, we recently established the essential metabolism including the transport of required nutrients from the environment, the gene map, and genome-wide proteomics. Of the 452 protein-coding genes, 143 are assigned to metabolism and 212 are assigned to genetic information processing. Using genome-wide proteomics and experimentally measured kinetic parameters from the literature we present here kinetic models for the genetic information processes of DNA replication, replication initiation, transcription, and translation which are solved stochastically and averaged over 1,000 replicates/cells. The model predicts the time required for replication initiation and DNA replication to be 8 and 50 min on average respectively and the number of proteins and ribosomal components to be approximately doubled in a cell cycle. The model of genetic information processing when combined with the essential metabolic and cell growth networks will provide a powerful platform for studying the fundamental principles of life.